2009
DOI: 10.1038/jid.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XVII Participates in Keratinocyte Adhesion to Collagen IV, and in p38MAPK-Dependent Migration and Cell Signaling

Abstract: Collagen XVII (COL17) participates in keratinocyte adhesion and possibly migration, as COL17 defects disrupt keratinocyte-basal lamina adhesion and underlie the disease non-Herlitz junctional epidermolysis bullosa. Using small interference RNA (siRNA) to knock down COL17 expression in HaCaT cells, we assessed cell characteristics, including adhesion, migration, and signaling. Control and siRNA-transfected keratinocytes showed no difference in adhesion on plastic dishes after incubation for 8 hours in serum-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Conversely, the shed ectodomain of Col XVII has been demonstrated to promote squamous cell carcinoma cell transmigration (49,53). Moreover, one group has shown that GABEB cells lacking apparent Col XVII expression demonstrate a migratory phenotype, whereas another has provided data indicating that Col XVII knockdown inhibits migration via reduced signaling to p38 MAPK (11,22). Our data are consistent with the latter report because they indicate that Col XVII loss induces motility and signaling defects in keratinocytes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Conversely, the shed ectodomain of Col XVII has been demonstrated to promote squamous cell carcinoma cell transmigration (49,53). Moreover, one group has shown that GABEB cells lacking apparent Col XVII expression demonstrate a migratory phenotype, whereas another has provided data indicating that Col XVII knockdown inhibits migration via reduced signaling to p38 MAPK (11,22). Our data are consistent with the latter report because they indicate that Col XVII loss induces motility and signaling defects in keratinocytes.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, our recent study presented evidence indicating that BPAG1e, one of the two bullous pemphigoid antigens that interact with ␣6␤4 integrin, is also required for signaling to Rac and, hence, plays a role in directed skin cell migration (17). In contrast, the role of Col XVII, the second bullous pemphigoid antigen, in regulating cell migration is quite controversial with contradictory reports in the literature (11,22).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…First, the present study and other investigations showed that collagen IV is also a relevant ligand for the Ecto-ColXVII. 18 Second, when artificial blistering of human skin is induced by 1 mol/L NaCl, collagen XVII separates to the epidermal side of the blister and not to the dermal side with laminin 332. 33,34 Also, the Ab HK139 detected the shed Ecto-ColXVII on the epidermal side of 1 mol/L NaCl split skin, 17 suggesting that yet other epidermisassociated molecules interact with the Ecto-ColXVII.…”
Section: Discussionmentioning
confidence: 99%
“…A study of HaCaT keratinocytes proposed a p38MAPK-dependent functional relationship between collagen XVII and collagen IV and/or other components in Matrigel (BD Biosciences, Franklin Lakes, NJ) that regulates cell attachment and migration. 18 Furthermore, an in vitro solid-phase protein-protein binding assay using recombinant collagen XVII fragments and laminin 332 indicated an affinity of collagen XVII carboxyl terminus with laminin 332. 19 Despite the limitations of such assays, the suggestion of a partnership between these two HD components is intriguing and has high pathophysiologic significance because aberrant expression of laminin 332 and collagen XVII has been suggested to be involved in the invasion and proliferation of various cancer cells.…”
mentioning
confidence: 99%